Implementasi Electronic Traffic Law Enforcement (ETLE) di Wilayah Hukum DITLANTAS Polda Riau - Zahra Aulia Putri; Ratna Dewi (Yayasan Almanar Pujud, 2024)
The establishment of ETLE is a technological development carried out from manual (conventional) ticketing to electronic ticketing (ETLE) with the aim of preventing extortion and traffic accidents. This study aims to determine the analysis of the implementation of Electronic Traffic Law Enforcement (ETLE) in Pekanbaru City and what are the obstacles in the implementation of Electronic Traffic Law Enforcement (ETLE) in Pekanbaru City. This research method uses a qualitative descriptive method with data collection from interviews, observations and documentation. This study uses Edward's theory with the indicators used, namely: Communication, Resources, Disposition, Bureaucratic Structure. The results of this study indicate that the Implementation of Electronic Traffic Law Enforcement (ETLE) in the Riau Police Traffic Directorate Jurisdiction has been carried out properly and as it should be, but there are several obstacles such as less than optimal communication between the police and the public regarding ETLE, the limited ETLE facilities in arresting traffic violators.